Prestasi akademik pada anak dengan gangguan pemusatan perhatian dan hiperaktivitas di sembilan sekolah dasar swasta di Kota Manado - Rumambi, Putri Ch.; Munayang, Herdy; Kaunang, Theresia M. D. (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2019)
Objective: The aim of this study is to find out the academic achievement in children with ADHD in nine private primary schools in Manado.Method: This research is an analytic study using cross sectional design to collecting data and using questionnaires from teachers and parents.Result: Total respondents who allowed their children sampled were 185 people in 9 different private schools in Manado, and total children with ADHD is 37 people. In this research there was 1 child with Inattension type, 25 with Hyperactivity type and 11 children with Combination type. Sex ratio of ADHD is 26 boys and 11 girls. Academic achievement of children with ADHD compared to non ADHD was found in mathematics subjects 14 children with ADHD and 8 non ADHD had grades below the standart, and in Indonesian subjects there were 24 children with ADHD and 9 children non ADHD had grades below the standart. Conclusion: In this study the academic achievement of children with ADHD is lower than children non ADHD.Keywords: Academic achievement, ADHD, report grades